Characterization of Physiological and Biochemical Attributes of Neem (Azadirachta indica A. Juss) under Salinity Stress - Muhammad Akram; Zunera Sajid; Abu Bakr Umer Farooq; Iftikhar Ahmad; Aftab Jamal; Humaira Rizwana; Bandar M. Almunqedhi; Domenico Ronga (Horticulturae, 2024)
Salinity poses a significant threat to agricultural productivity worldwide, with its detrimental effects on plant growth and physiological processes. Understanding the mechanisms by which plants respond to salt stress is crucial for developing strategies to mitigate its impact on crop yield and sustainability. To address this issue, a pot study was conducted to determine the effect of salt stress on the physiological and biochemical attributes of neem (Azdiarchta indica A. Juss). Plants were grown for 10 months in pots filled with soil having different salinity levels of 3, 6, 9, 12, 15, and 18 dS m−1 and compared with a control of 1.7 dS m−1. The results showed that plant growth and chlorophyll contents declined as salinity levels increased. Due to oxidative stress, the contents of H2O2 increased under higher salt levels. The mitigation of oxidative stress was achieved through the activation of antioxidant enzymes (catalase, ascorbate peroxidase, peroxidase, and superoxide dismutase). Multivariate analysis indicated that Na+ accumulation in plants was positively related to H2O2 production and enzymatic activities, and negatively related to plant biomass, chlorophyll contents, root and shoot K+ concentration, and root K+/Na+. The experimental results suggest that neem plants can be grown in moderate saline soils.